Reaction Products of Crude Palm Oil-based Fatty Acids and Monoethanolamine as Corrosion Inhibitors of Carbon Steel - Ali, Mohamad Makrus; Irawadi, Tun Tedja; Darmawan, Noviyan; Khotib, Mohammad; Mas’ud, Zainal Alim (Makara Journal of Science, 2019)
Herein we report the application of the reaction products of crude palm oil-based fatty acids and monoethanolamine as sustainable corrosion inhibitors in acidic environments for carbon steels. Reaction products were identified based on FTIR analysis as a mixture of 2-aminoethyl fatty esters and N-(2-hydroxyethyl) fatty amides. Corrosion inhibition effect of these compounds was evaluated by potentiodynamic polarization techniques in 0.5 M HCl. The mixture of fatty esters and fatty amides showed promising potential as an alternative corrosion inhibitor. Inhibition efficiency was found to be 80% at 80 ppm. Thermodynamic and kinetic parameters obtained from the tafel plot displayed an increase in activation energy with a higher inhibitor concentration that led to the decrease in the corrosion rate. Furthermore, physisorption interaction was found to be the main process of the inhibitor’s adsorption on metal surfaces and obeyed the adsorption model of the Langmuir isotherm.